2021
DOI: 10.48550/arxiv.2111.11688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entanglement between two evaporating black holes

Akihiro Miyata,
Tomonori Ugajin

Abstract: We study a thermo-field double type entangle state on two disjoint gravitating universes, say A and B, with an eternal black hole on each. As was shown previously, its entanglement entropy of the universe A is computed by the generalized entropy on a new spacetime constructed by suitably gluing the black holes on A and B. We study such spacetime gluings when universes are asymptotically flat and AdS cases, especially when the masses of these black holes are different. We also clarify the rule to construct such… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…We will see the exact match of the combinations of modified cosmic branes in AdS 3 bulk from proposals in eqs. ( 40),( 42) and (44). Our results then indicate that the island for reflected entropy and entanglement negativity match with each other for general 2D black holes coupled with CFT matters.…”
Section: Consistency Check Of Island Formula Of Entanglement Negativi...supporting
confidence: 68%
See 2 more Smart Citations
“…We will see the exact match of the combinations of modified cosmic branes in AdS 3 bulk from proposals in eqs. ( 40),( 42) and (44). Our results then indicate that the island for reflected entropy and entanglement negativity match with each other for general 2D black holes coupled with CFT matters.…”
Section: Consistency Check Of Island Formula Of Entanglement Negativi...supporting
confidence: 68%
“…Proposal eq. (44) states that E(A : B) is given by the combination of the following generalized entanglement entropies…”
Section: Phase-ivmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another possibility is turning on gravity in the reservoir -without requiring double holography (see work starting with [31,32]) -and subsequently testing whether an ERB forms dynamically. In [32], it was shown that black holes evaporating into gravitating baths in certain toy models feature a Hawking-Page-like [33] transition after the Page time; of particular relevance is the work of [34,35], which started out with boundary conditions for two gravitating universes in JT gravity in the state (1.2) and showed that a Euclidean path integral preparation gave a dominant connected geometry for the computation of the von Neumann entropy. Yet another approach to connect the black hole to the radiation was made in [36], relying crucially on an end-of-the-world brane to cap off the black hole spacetime at r > 0.…”
Section: Introductionmentioning
confidence: 99%
“…See also [4] for a very nice review on the topic. Furthermore, the rule were applied in de Sitter spacetime [58][59][60][61][62][63], flat-space cosmology 4 [64] and separate universes [49,53,[65][66][67].…”
Section: Introductionmentioning
confidence: 99%